The metaphors of collaboration, or the social construction of collaborative interactions between health professionals - Tomelleri, Stefano; Lusardi, Roberto; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2015)
This article illustrates the ways in which symbolic representations of reality, embodied in metaphors and language, can affect collaborative interactions in the current situation of social and economic change. We assume that corporate transformation and organizational configurations influence health professionals’ representations in largely unconscious ways  and, with these, their everyday practice. On the basis of empirical data collected through 13 focus groups in an Italian hospital, our intention is to show the extent to which joint working can be linked to three main metaphors each matching specific forms of social and professional interaction. The three metaphors of collaboration constitute different attempts to interpret social and organizational changes in proactive - encouraging social innovation - or defensive terms - as actions of cultural resistance. The three metaphors are: apparatus, family and team. In different ways, the first two represent forms of resistance to change and are widely present within organizations. The latter, on the other hand, consists of a proactive way to deal with ongoing social and organizational change. This metaphor testifies to the existence of a different approach to collaborative interactions, a perspective related to specific combinations of organizational and professional characteristics. This study indicates that organizational change and collaboration can be strengthened by metaphors that illustrate open, plural and highly heterogeneous professional settings.